Enhanced Hydrothermal Depolymerization with Fe/Ni Loaded C Catalysts for Improving Anaerobic Digestion Performance of Corn Stover - Xitong Wang; Chenyang Zhu; Hairong Yuan; Xiujin Li (Energies)
This research investigated the effects of hydrothermal depolymerization with Fe/Ni loaded C catalysts on the anaerobic digestion (AD) performance of corn stover (CS). CS was depolymerized at 140 °C for 20 min with Fe/C or Ni/C catalysts, and then anaerobically digested. The results showed that the biomethane yield with Fe/C-600 increased by 36.6% compared to that of the control. This increase could be attributed to effective CS depolymerization with catalysts (DC), indicated by modified structures of solid fraction and enriched available components of liquid fraction. SEM analyses showed that CS microphysical structure after DC was obviously disrupted, resulting in more accessibility of cellulose and hemicellulose. The crystallinity index (CrI) of depolymerized CS was significantly reduced from 32.5% to 23.5%, allowing for a more easily biodegradable non-crystalline area to be available for enzymes. Meanwhile, the DC group produced 4.7 times more reducing sugar (RS), and a 3.4 times increase in total volatile fatty acids (VFAs) as compared to the control. Furthermore, these enhancements in DC led to an increased relative abundance of cellulolytic bacteria (Hydrogenispora and Fermentimonas) and anaerobic methanogenic archaea (Methanosarcina) in following the AD process. This could explain the reason for the biomethane yield increase with DC from microbial perspectives. This study demonstrated that hydrothermal depolymerization with Fe/C or Ni/C could provide an effective approach for obtaining more biomethane from CS via AD.